HEALTH-PRESERVING BEHAVIOR AS A MANIFESTATION OF PSYCHOLOGICAL RESILIENCE IN FAMILY SYSTEMS (Psychology Travelogs, 2025)
The article presents a theoretical and psychological analysis of health-preserving behavior as a manifestation of the psychological resilience of the family system under crisis conditions. It is emphasized that such behavior is not a purely individual phenomenon, but a systemic one, forming and functioning within the structure of interpersonal interaction, emotional support, and value coordination within the family. The research is based on an interdisciplinary methodology, including systemic, ecological-contextual, and resource-based approaches, which allow a comprehensive understanding of the mechanisms of adaptation in the family environment.The article substantiates that family resilience performs the function of an internal psychological resource, enabling the maintenance of structural integrity, emotional balance, and functional organization during periods of socio-psychological instability. It includes cognitive-meaning-making, emotional-regulatory, behavioral-organizational, and communicative domains that jointly influence the formation of health-oriented motivation, modeling of adaptive behavior, and joint responsibility for the well-being of all family members.A conceptual model is proposed, demonstrating the two-way connection between family resilience and health-preserving behavior: resilience acts as a determinant of behavioral patterns, while these patterns in turn reflect the level of systemic functionality. Health-preserving behavior is interpreted as a stabilization mechanism that supports biopsychosocial homeostasis and the long-term viability of the family under stress. The findings may be used in psychological diagnosis, psychoeducation, counseling, and prevention in the context of family support under crisis.
Keywords: resilience; family system; health-preserving behavior; adaptation; stress; behavioral regulation; family interaction; crisis psychology